Developing Case Study-Based Microlearning through V-Learn to Enhance Language Politeness in Students - Putra, A.A. Putu Eka; Arief, Nur Fajar; Rani, Abdul; Tabrani, Akhmad (Fakultas Ilmu Pendidikan Universitas PGRI Kanjuruhan Malang, 2024)
The research will describe the development of case-based microlearning learning video media as well as the validity and effectiveness of the product to improve the understanding of politeness in students. This research is a developmental research (RnD) using the ADDIE model. The research subjects are one learning planner, one learning media expert, one study material expert, and twenty-five small-group experimental students. The data collection method uses documentation recording, interview methods, observation methods, and questionnaire methods. Research instruments use document recording sheets, questionnaires, and interview sheets. The data analysis used is qualitative descriptive analysis and quantitative description analysis. The results of the study were the development of a case study based microlearning video learning media using the ADDIE development stage, as well as the validity results on the learning planners obtained a score of 86% with good qualification, the learning media experts obtaining a rating of 96% with excellent qualifications, learning material experts obtaining a rate of 95% with excellent qualifying, the skilled professionals obtain the score of 93% with very good qualifications. So, the case study-based microlearning learning video media is worthy of use in learning.